(untitled) (Fiep Bulletin - online, 2014)
The decisions of teachers on Physical Education (PE) in elementary school are influenced by multiple factors involving personal and professional lives of teachers. Thus, regularity, quality and sustainability of PE provided to students varies widely, depending on a few factors more than others according to the perception of teachers. Data were collected with a questionnaire applied a stratified group of 150 elementary teachers (21 male and 129 female), divided into groups of 30 as to teaching experience – less than 5, between 6 - 10, 11 - 15, 16 - 21, and more than 21. Data presented here result from answers to one question, 21 traces that influence the decisions about PE practices. The results identify two sets of traces of the personal and professional lives of teachers that influence decisions in PE: personal characteristics (attitudes, beliefs, tastes, teaching satisfaction and experience), institutional nature (professional association/union), school organization (school inspector, school coordinator) and of social impact (image next to peers).